EVALUASI KUALITAS INSTRUMEN TES DALAM PEMBELAJARAN GEOGRAFI DI MAN 2 KOTA BATU - Wijayanto, Pradika Adi; Allifah, Aimmaul; Amirrudin, Ach (Universitas Negeri Semarang, 2016)
This study aims to determine the quality of the test instrument. The instrument could be qualified and worthyif meets certain requirements include good quality language, validity, reliability, level of difficulty, anddistinguish. Data used in the form of daily test questions code A and B geography class X IPS MAN 2 KotaBatu. This is evaluative research. Based on the survey results revealed (1) the test instrument in accordancewith the basic competencies and learning indicators; (2) the language quality which used in daily geographytest still less valid; (3) the validity of the test questions was not good yet; (4) The coefficient reliabilitybetween code A and B questions are medium; (5) code A questions dominated by easy level of difficulty whilecode B questions dominated by medium level of difficulty; (6) distinguish power of the questions showed thatboth code A and B were bad.